(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2010)
Umbilical cord blood (UCB) is a source of premature haemopoietic stem cells (HSC) and progenitor cells which has a tremendous capacity to differentiate into another type of cell. Many malignant and non-malignant disorders are being treated with the transplantation of the UCB cells. This precious thing is usually discarded. But it can be easily and safely collected, cryopreserved and stored in a cord blood bank. UCB banks are being established in many countries of the world. Two models of cord blood banking systems are available-one is Family or private banking where UCB is stored for the benefit of the donor or their family and another is non-profitable public banking where UCB is stored for research purpose and for allogeneic unrelated transplantation. About seventy diseases can be treated with UCB transplantation. But, there are many debates regarding cord blood transplantation and legal and ethical issues cause to concern. However, UCB has become an established alternative to bone marrow transplantation in children and young adults. Key words: Stem cell, cord blood banking, stem cell transplantation. DOI: 10.3329/jbcps.v27i1.4242 J Bangladesh Coll Phys Surg 2009; 27: 39-44